(untitled) (Research, Society and Development, 2020)
This article aims to describe the experience of two undergraduate students, a professor and a psychologist, in the development of an extension project on the promotion of dialogue as a way of preventing suicide. The themes worked on were conceptualization, the motive that is happens, who is more vulnerable, stressors, myths, and truths about suicide, what services to seek and how to help someone with suicidal ideation. 109 students from the first year of high school participated in the activities. The activity provided an approximation and demystification of some important points on the topic of suicide in adolescence. In addition, it was possible to show the group routes to prevent suicide and thus value life.